Extended local anesthesia enabled by flavonoid permeation enhancers - Yiyuan Han; Matthew Torre; Xiaojing Ma; Tianrui Xue; Yuan Wang; Sooyeon Jo; Akie Fujita; Bruce P. Bean; Daniel S. Kohane (Proceedings of the National Academy of Sciences, 2026)
Site 1 sodium channel blockers (S1SCBs), such as tetrodotoxin (TTX) and neosaxitoxin, are ultrapotent local anesthetics with low tissue toxicity. Their duration of action is relatively brief, but increasing the dose can lead to systemic toxicity. Here, we report that selected flavonoids—puerarin (PUE), naringenin, and kaempferol—prolong nerve block from S1SCBs 4- to 25-fold. Using both tympanic membrane (TM) permeation and sciatic nerve fluorescence distribution models, we demonstrate the flavonoids increase drug penetration across biological barriers (the TM and the barriers in and around nerve), suggesting that they act as chemical permeation enhancers (CPEs). Importantly, flavonoids exhibited minimal tissue toxicity compared to conventional CPEs. Coencapsulation of TTX and PUE into a liposomal delivery system further prolonged local anesthesia to over 25 d from a single injection. These findings establish flavonoid compounds as a safe class of CPEs and provide a platform of long-acting, nonopioid pain therapies. Flavonoids may be attractive alternatives to conventional CPEs in biomedical applications.